Tasmanian Supreme Court 1850-1899 - Finnane, Mark (ADA Dataverse, 2020)
Trials on indictment at Tasmanian Supreme Court from 1850-1899. The data was sourced by the Prosecution Project principally from court registers and record books held at Tasmanian Archives and Heritage Office, and data collection was by Chris Leppard-Quinn. Later curation of the records has included checking against Trove (https://trove.nla.gov.au/) database of digitised newspapers as well as some secondary sources. This dataset includes for most cases url links to the original records available online at TAHO.